2020
DOI: 10.1186/s13059-020-02201-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous epigenetic perturbation and genome imaging reveal distinct roles of H3K9me3 in chromatin architecture and transcription

Abstract: Introduction Despite the long-observed correlation between H3K9me3, chromatin architecture, and transcriptional repression, how H3K9me3 regulates genome higher-order organization and transcriptional activity in living cells remains unclear. Result Here, we develop EpiGo (Epigenetic perturbation induced Genome organization)-KRAB to introduce H3K9me3 at hundreds of loci spanning megabases on human chromosome 19 and simultaneously track genome organiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…5f, Additional file 1: Figure S15). This is consistent with previous suggestions that H3K9me3 play a limited role in gene repression [44][45][46] and the likely presence of other epigenetic modifications regulating the expression of the genes in the PCH.…”
Section: Broad Pericentromeric Heterochromatin Domainssupporting
confidence: 93%
“…5f, Additional file 1: Figure S15). This is consistent with previous suggestions that H3K9me3 play a limited role in gene repression [44][45][46] and the likely presence of other epigenetic modifications regulating the expression of the genes in the PCH.…”
Section: Broad Pericentromeric Heterochromatin Domainssupporting
confidence: 93%
“…Importantly, if a gene locus that becomes relocated to the nuclear periphery and silenced during differentiation is artificially moved to the nuclear periphery outside of a differentiation context, it does not become silenced [ 72 , 74 ]. Similarly, although CAS9-mediated increases in H3K9 methylation across a large region of human chromosome 19 can induce the formation of heterochromatin-like domains, this large-scale change in chromatin structure did not result in widespread gene repression [ 20 ]. From these various studies, it appears that although increased H3K9 methylation may associate with transcriptional suppression, direct regulation of gene expression falls to protein factors (activators/repressors) located in the various nuclear compartments during specific developmental windows; not by a change in histone methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Although H3K9me2-enriched regions of the genome associate with gene silencing, heterochromatin also protects chromosome integrity during cellular stress [ 19 ]. Further, recent studies indicate that increased H3K9 methylation and formation of heterochromatin-like domains do not necessarily result in widespread gene repression [ 20 ]. Work in multiple organisms, including C. elegans , have demonstrated that the effects of early-life mitochondrial dysfunction and oxidative stress persist throughout the lifespan [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…(35) also showed that removal of the H3K9me3 histone modification leads to loss of HP1 co-localisation, but the heterochromatin foci remain intact (inconsistent with HP1 begin a driver of heterochromatin body formation). Other work (40) has suggested that while HP1 may not be necessary to compact large satellite repeat heterochromatin regions, it is required to compact and silence smaller H3K9me3 marked segments within otherwise active regions. The function of HP1 clearly still not well understood.…”
Section: Discussionmentioning
confidence: 99%